Reduced PAX2 expression in murine fallopian tube cells enhances estrogen receptor signaling - Colina, Jose A (Carcinogenesis, 2020)
High-grade serous ovarian cancer (HGSOC) is thought to progress from a series of precursor lesions in the fallopian tube epithelium (FTE). One of the preneoplastic lesions found in the FTE is called a secretory cell outgrowth (SCOUT), which is partially defined by a loss of paired box 2 (PAX2). In the present study, we developed PAX2-deficient murine cell lines in order to model a SCOUT and to explore the role of PAX2 loss in the etiology of HGSOC. Loss of PAX2 alone in the murine oviductal epithelium (MOE) did not induce changes in proliferation, migration and survival in hypoxia or contribute to resistance to first line therapies, such as cisplatin or paclitaxel. RNA sequencing of MOE PAX2(shRNA) cells revealed significant alterations in the transcriptome. Silencing of PAX2 in MOE cells produced a messenger RNA expression pattern that recapitulated several aspects of the transcriptome of previously characterized human SCOUTs. RNA-seq analysis and subsequent qPCR validation of this SCOUT model revealed an enrichment of genes involved in estrogen signaling and an increase in expression of estrogen receptor α. MOE PAX2(shRNA) cells had higher estrogen signaling activity and higher expression of putative estrogen responsive genes both in the presence and absence of exogenous estrogen. In summary, loss of PAX2 in MOE cells is sufficient to transcriptionally recapitulate a human SCOUT, and this model revealed an enrichment of estrogen signaling as a possible route for tumor progression of precursor lesions in the fallopian tube.